2000
DOI: 10.1016/s0014-5793(00)01089-9
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐induced phospholipase A2 activation and arachidonic acid mobilization in P388D1 macrophages

Abstract: We have found that chitosan, a polysaccharide present in fungal cell walls, is able to activate macrophages for enhanced mobilization of arachidonic acid in a dose-and timedependent manner. Studies aimed at identifying the intracellular effector(s) implicated in chitosan-induced arachidonate release revealed the involvement of the cytosolic Group IV phospholipase A 2 (PLA 2 ), as judged by the inhibitory effect of methyl arachidonoyl fluorophosphonate but not of bromoenol lactone. Interestingly, priming of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…NK cells are known to be involved in clearance of cells infected with intracellular pathogens, but the relevance of NK cells in our model is unclear. Limited but detectable macrophage infiltration was observed in the footpads of animals not sensitized with C. albicans and challenged with chitosan, indicating that macrophages may respond to stimulation by chitosan directly and independently of T-cells, probably through innate immune receptors, as has been demonstrated in the literature (Bianco et al, 2000;Peluso et al, 1994) Given the flexibility, consistency, and sensitivity of the ex vivo ELISPOT-based DTH assay, this method provides a great complement to the more traditional in vivo footpad swelling DTH assay in adult rats, and offers clear advantages for immunotoxicity testing in neonatal/juvenile animals. Further validation of this model using a range of immunotoxic compounds with known effects in humans is needed.…”
Section: Discussionsupporting
confidence: 54%
“…NK cells are known to be involved in clearance of cells infected with intracellular pathogens, but the relevance of NK cells in our model is unclear. Limited but detectable macrophage infiltration was observed in the footpads of animals not sensitized with C. albicans and challenged with chitosan, indicating that macrophages may respond to stimulation by chitosan directly and independently of T-cells, probably through innate immune receptors, as has been demonstrated in the literature (Bianco et al, 2000;Peluso et al, 1994) Given the flexibility, consistency, and sensitivity of the ex vivo ELISPOT-based DTH assay, this method provides a great complement to the more traditional in vivo footpad swelling DTH assay in adult rats, and offers clear advantages for immunotoxicity testing in neonatal/juvenile animals. Further validation of this model using a range of immunotoxic compounds with known effects in humans is needed.…”
Section: Discussionsupporting
confidence: 54%
“…LPS present in TE was determined by using the Endosafe Limulus Amebocyte Lysate test (Charles River Laboratories Wilmington, DE), and was similar to that of complete RPMI 1640 medium supplemented with 10% fetal calf serum (FCS; Gibco, Gran Island, NY), 50 µM 2-mercaptoethanol (Sigma-Aldrich, St Louis, MO) and 50 µg/ml Gentamicin (Gibco). CII was prepared as described [15]. CpG-ODN 1826 was purchased from OPERON (Huntsville, AL).…”
Section: Methodsmentioning
confidence: 99%
“…The relatively higher values observed for CBC when compared to commercial dressings may be related to the effect of the material bioconversion products, but also to a certain pro-inflammatory activity of CBC [90]. Bianco et al [91] reported that chitosan could mediate macrophage activation through the release of arachidonic acid (AA) and even found higher levels of cytokines released from LPSstimulated cells in the presence of chitosan. Moreover, it was found that chitosan amino groups are recognized by the immune system and that macrophages are activated to various extents by chitin derivatives.…”
Section: Cytocompatibility and Anti-inflammatory Activitymentioning
confidence: 99%